MEASURING POVERTY IN AN ULTRAPERIPHERAL REGION - THE CASE OF THE CANARY ISLANDS - Delia Davila Quintana; Santiago Rodriguez Feijoó; Alejandro Rodriguez Caro; Vanessa del Pino González García (European Regional Science Association (ERSA), 2005)
The Canary Islands (one of Spain's 17 autonomous communities) is considered in the EC Treaty "ultra-peripheral region" which means: i) differences in the development processes and integration that justify certain specific policies (six out of the seven regions involved are among the poorest in the EU). This is related with remoteness, insularity, small size, difficult topography and climate, and the dependence on a small number of products; ii) the remoteness from the mainland countries and climatic conditions (tropical or subtropical) and, iii) the role of EU frontier and the geographical structure characterized by size and distance. With data of the Survey of Social Conditions (2001) we study the income inequality of individuals in The Canary Islands. Individuals are divided into various subgroups along several dimensions, such as island of residence, age, employment status etc. The difference in inequality between and within the various subgroups is studied using absolute-relative poverty line. We estimate poverty using a subjective approach too, where the level of the poverty line is derived using the opinion of the individual, rich or poor, on poverty. The subjective poverty line used is the Leyden Poverty Line based on subjective questions regarding income and economic welfare.
Keywords: 330